2020
DOI: 10.3390/nu12082180
|View full text |Cite
|
Sign up to set email alerts
|

β-Cryptoxanthin Improves p62 Accumulation and Muscle Atrophy in the Soleus Muscle of Senescence-Accelerated Mouse-Prone 1 Mice

Abstract: We investigated the effects of β-cryptoxanthin on skeletal muscle atrophy in senescence-accelerated mouse-prone 1 (SAMP1) mice. For 15 weeks, SAMP1 mice were intragastrically administered vehicle or β-cryptoxanthin. At 35 weeks of age, the skeletal muscle mass in SAMP1 mice was reduced compared with that in control senescence-accelerated mouse-resistant 1 (SAMR1) mice. β-cryptoxanthin increased muscle mass with an increase in the size of muscle fibers in the soleus muscle of SAMP1 mice. The expressions of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The ratio of p62-positive fibers to p62-negative fibers in a CSA of the soleus muscle was also decreased in β-cryptoxanthin-administered SAMP1 mice compared with that in non-treated mice. Accordingly, muscle mass, CSA, and MHC type I protein levels in the soleus were increased in β-cryptoxanthin-treated SAMP1 mice compared with those in non-treated SAMP1 mice [98].…”
Section: Improvement In Maintenance Of Protein Homeostasis By Natural...mentioning
confidence: 87%
“…The ratio of p62-positive fibers to p62-negative fibers in a CSA of the soleus muscle was also decreased in β-cryptoxanthin-administered SAMP1 mice compared with that in non-treated mice. Accordingly, muscle mass, CSA, and MHC type I protein levels in the soleus were increased in β-cryptoxanthin-treated SAMP1 mice compared with those in non-treated SAMP1 mice [98].…”
Section: Improvement In Maintenance Of Protein Homeostasis By Natural...mentioning
confidence: 87%
“…β-Cryptoxanthin, a provitamin A carotenoid, suppresses atrophy of the soleus muscle, but not of the gastrocnemius, EDL, TA, and plantaris muscles, of senescence-accelerated mouseprone 1 mice. (43) In contrast, dietary lycopene up-regulates MyHC I gene expression and down-regulates MyHC IIb gene expression in both soleus and gastrocnemius muscles of mice. (44) CD36 is required for lycopene uptake in adipocytes and adipose tissue.…”
Section: Discussionmentioning
confidence: 97%
“…β-Cryptoxanthin, a provitamin A carotenoid, suppresses atrophy of the soleus muscle, but not of the gastrocnemius, EDL, TA, and plantaris muscles, of senescence-accelerated mouse-prone 1 mice.‍ ( 43 ) In contrast, dietary lycopene up-regulates MyHC I gene expression and down-regulates MyHC IIb gene expression in both soleus and gastrocnemius muscles of mice.‍ ( 44 ) CD36 is required for lycopene uptake in adipocytes and adipose tissue.‍ ( 45 ) The molecular mechanism by which lycopene is incorporated into the gastrocnemius muscle is unknown, but these results suggest that β-carotene, β-cryptoxanthin, and lycopene are incorporated into the soleus muscle via CD36.…”
Section: Discussionmentioning
confidence: 99%
“…BCX is a natural antioxidant that functions as an antiinflammation and anticancer agent [ 36 ]. A recent study noted that BCX improved muscle atrophy in the senescence-accelerated mouse-prone 1 mice, suggesting that BCX had anti-senescence effects [ 37 ]. In this study, we found that BCX reduced the number of SA-β-gal-positive cells, inhibited the expression of P16, P21, and P53, and reduced the production of the cellular senescence marker γ-H2AX in HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%